Malay traditional herbs : culinary and traditional medicinal practices. - Abdul Karim, Muhammad Shahrim; Ismail, Nurul Ashikin (Brunei Council of Social Welfare, 2012)
An article about various Malay traditional herbs and its benefits. Culinary practices are also discussed.